Early diagnosis of neonatal sepsis with special focus on leukergy test – A forgotten tool - Prakash, Anubhav; Richa, Richa; Narain, Bhupendra (Indian Journal of Child Health, 2019)
Background: Sepsis in newborn is a leading cause of mortality and morbidity. Neonates with one or more predisposing factors (namely, low birth weight, prematurity, foul-smelling liquor, prolonged rupture of membranes, and prolonged labor) are at increased risk of sepsis. Objective: The objective of the study was to establish laboratory tests that would help in the early diagnosis of neonatal sepsis with a special focus on leukergy test. Materials and Methods: The present study was a hospital-based prospective study involving 400 neonates admitted in the Neonatal Intensive Care Unit for clinically suspected sepsis, with different symptoms during the period of October 2018 to September 2019 at a government hospital of Bihar. In this study, we evaluated peripheral smear to establish an appropriate hematological parameter for diagnosis of neonatal sepsis even before blood culture. Results: The total neutrophil count was highly sensitive (77.8%) and increased band cell: Mature neutrophil ratio was highly specific (99.2%) for an early diagnosis of neonatal sepsis. The positive predictive value (PPV) was the highest for band cell: Mature neutrophil ratio (97.2%) and negative predictive value (NPV) were the highest for decreased platelet count (78.3%). Leukocyte adhesion/aggregation test had a sensitivity of 59.1%, specificity of 60.2%, PPV being 68.9%, and NPV of 49.5%. Conclusion: Positive leukergy test is a good predictor for early diagnosis of neonatal sepsis and can be used in resource poor settings with less time. Hematological parameters are good indicators for early diagnosis of neonatal sepsis. A group of tests is more reliable than any single parameter.